(untitled) (Scientific journal of the Fergana State University, 2023)
The article considers theories of vibrational relaxation in diatomic gases. When calculating the probability of vibrational-translational energy exchange, we based on the mechanism of binary collisions. On the basis of the mechanism of binary collisions, the processes of vibrational-translational relaxation were studied and the probabilities of energy exchange were calculated, as well as the dependences of the probability of exchange from temperature.